Herpes zóster Simuladores que pueden desviar nuestra atención - Vaglio Giors, Gisela; De Luca, David Aldo; Echeverría, María Eugenia; Baztán Piñero, María Carolina; Torre, Ana Clara; Galimberti, Ricardo Luis (Revista del Hospital Italiano de Buenos Aires, 2011)
.